Developing an Expert-Consensus Framework of Qawwam Leadership for Family Well-Being in Islamic Family Education - Zur Raffar, Izzah Nur Aida; Hamjah, Salasiah Hanin; Misrom, Azimah (Jurnal Pendidikan Agama Islam, 2026)
Purpose – This study aims to identify and validate the core elements of qawwam leadership that contribute to family well-being, and subsequently develop framework based on expert consensus to be applied within Islamic family education. The study also reconceptualises qawwam as a multidimensional responsibility encompassing emotional, material, relational, and spiritual dimensions. Design/methods/approach – This study employed a consensus-based quantitative design through the application of the Fuzzy Delphi Method (FDM). A total of 14 preliminary items related to qawwam leadership were developed through a comprehensive literature review, expert consultations, and focus group discussions before being evaluated by a panel of 15 multidisciplinary experts. Item evaluation was conducted based on three principal FDM indicators, namely threshold value (d ≤ 0.20), expert consensus level (≥75%), and defuzzification value. Findings –  The findings indicate that all 14 proposed items achieved a high level of expert consensus and fulfilled the established acceptance criteria of the Fuzzy Delphi Method (FDM). The analysis revealed that qawwam leadership constitutes a multidimensional responsibility encompassing emotional, material, relational, and spiritual dimensions. Collectively, these dimensions highlight the role of qawwam as a framework that fosters trust, care, responsibility, and family well-being within the context of contemporary Muslim families. Research implications/limitations –  This study contributes to the field of Islamic family education by providing a theoretically grounded and operational framework of qawwam leadership that can guide the development of premarital education programmes, family counselling interventions, and community-based family development initiatives. The framework emphasises emotional, relational, material, and spiritual responsibilities, offering a systematic reference for promoting family well-being and strengthening leadership roles within contemporary Muslim families. Originality/value –   This study contributes theoretically by developing a multidimensional qawwam leadership framework that integrates trust, emotional care, relational responsibility, and family well-being. The framework expands the understanding of the qawwam concept and provides a foundation for future research and the development of Islamic family education models oriented towards family well-being.